The Mediterranean Inclination in the Archaeological and Epigraphical Profile of Tróia (Setúbal, Portugal) - Teixeira, Sílvia (2017)
The Roman site of Tróia (Setúbal, Portugal) has been capturing the interest of researchers since the 16th century, especially in what concerns the archaeological structures and remains, with comparatively little attention having been given to its epigraphical record. However, this kind of data has proven valuable in approaching the topic of the exchanges between Tróia and other parts of the Empire, particularly the Eastern Mediterranean and Northern Africa, most notably the latter. By giving epigraphy its well-deserved importance as a source of information, this paper aims to combine the data provided by the inscriptions with the archaeological and historical data, in order to obtain a more complete economic and sociocultural portrayal of the Roman Tróia, and to assess the reflection of the Mediterranean influences in its archaeological and epigraphical profile. Elements such as the industrial architecture, funerary and religious structures and rituals, ceramic ware, demographic and onomastic data, will therefore come together in order to provide a comprehensive outline of this insular settlement of the Atlantic seaboard as an extension of the Mediterranean world.